Cross currents a documentary - Deocampo, Nick (Center for New Cinema, 2012)
Documentaries on environmental stories shots in five ecological sites in Batanes (Philippines), Biwako (Japan), Kali Code (Indonesia), Khiriwong (Thailand), and Tasik Chini (Malaysia). It featuring bearers of local wisdom that may yet provide new perspectives that will give hope for survival in the evolving find of new ecology.